Pengaruh Ukuran Perusahaan, Leverage, dan Net Profit Margin (NPM) terhadap Perataan Laba (Income Smoothing) pada Perusahaan Keuangan yang Terdaftar di BEI - Alexandra, Vinniex Veronica (STIE Perbankan Indonesia, 2024)
The research was conducted to determine the effect of firm size, financial leverage, and the Net Profit Margin (NPM) on the practice of income smoothing in financial companies listed on the Indonesia Stock Exchange (IDX). The sample in this study were financial companies listed on the Indonesia Stock Exchange (IDX) during the years 2007-2010. Data were collected through purposive sampling. The analysis is carried out using multiple linear regression and t-tests, with the first test of classical assumptions. Through multiple linear regression analysis, it is known that the variable Net Profit Margin (NPM) has a significant influence on the practice of income smoothing. This is indicated by the regression relationship between the dependent variable with several independent variables and a significance value smaller than 0.05. While the firm size variable and financial leverage has no effect on the practice of income smoothing because it has a significance value greater than 0.05. Keywords: firm size, financial leverage, Net Profit Margin (NPM), income smoothing